Whose rules? Whose power? The Global South and the possibility to shape international peacekeeping norms through leadership appointments. Issue 4 (13th October 2022) - Harig, Christoph; Jenne, Nicole
Abstract: International organisations reflect global power configurations and as such, are deemed to reproduce global inequalities. Nevertheless, they also represent opportunities for the Global South to challenge the global stratification of power, for instance by providing personnel to international agencies and bureaucracies. This article examines the role of leadership personnel from the Global South in implementing robust peacekeeping mandates. Given that states from the Global South have often been hesitant to support the use of force internationally, can leadership positions in peace operations help these states to influence norms at the implementation level? We develop a conceptual understanding of individuals' role in implementing norms and apply the framework to military force commanders from Brazil, India, and Rwanda. The analysis demonstrates that appointments provide an opportunity for norm contestation, but do not necessarily guarantee such influence. Under certain circumstances, we find that military force commanders can actually undermine their governments' preferences. However, the relation between force commanders' practices and their country of origin's policy stance is complex and influenced by a variety of different factors that merit further investigation.